Estimating growth patterns and driver effects in tumor evolution from individual samples - Leonidas Salichos (Nature Portfolio, 2020)
There are many methods to detect cancer-driving mutations. Here, the authors harness the variant allele frequency of mutations in tumor cells of a single individual to present a method that can estimate growth patterns and identify driver gene evolution at a patient specific level.